Centro de referência paralímpico: a inclusão da pessoa com deficiência na prática esportiva no Centro-Oeste brasileiro - Souza, Glauber Henrique de Almeida (2025)
This study aimed to examine the development of the Brazilian Paralympic Reference Centers (CRPB) in the Central-West region of Brazil, from their implementation to the year 2024. The research was conducted in three methodological stages. In the first stage, a documentary and bibliographic study was undertaken to identify the objectives and guiding principles of the CRPBs, through the analysis of technical and strategic reports containing relevant information on the progress of the centers between 2019 and 2024. The second stage consisted of a survey involving five CRPB coordinators—one from each Federative Unit in the Central-West region—with the exception of Goiás, where two coordinators were interviewed. The interviews sought to examine the profiles of the individuals served by the program; the conditions for teaching Paralympic sports; strategies for student recruitment; the relationship between competitions and family involvement; athletes’ social and personal aspects; and team composition. In the third stage, an interview was conducted with a national supervisor from the Brazilian Paralympic Committee to identify the challenges and milestones associated with the expansion and operation of the centers. The findings indicate that the inclusion of people with disabilities in the CRPBs is being implemented effectively, with teams dedicated to delivering high-quality support to ensure that students benefit from the expertise of each staff member. However, not all centers have complete teams to fully provide these benefits, as some remain in the early stages of implementation and lack even internship positions. It was concluded that the CRPBs are undergoing rapid expansion, reaching smaller municipalities and increasingly benefiting students. By 2024, the centers had reached a total of 9,240 students/athletes across Brazil, of whom 952 were located in the Central-West region, participating in 14 different sports disciplines. This expansion aims to foster the widespread development of Paralympic sports, from grassroots to high-performance levels, throughout the region.